Alterations of telomere length and DNA methylation in hairdressers: A cross‐sectional study. (6th December 2015) - Li, Huiqi; Åkerman, Gabriella; Lidén, Carola; Alhamdow, Ayman; Wojdacz, Tomasz K.; Broberg, Karin; Albin, Maria
Abstract : Working as hairdressers has been associated with increased risk for cancer, particularly bladder cancer. To evaluate if current hairdressers have elevated risks of adverse health effects, we measured several biomarkers related to cancer‐related DNA alterations. We enrolled 295 hairdressers and 92 non‐hairdressers (all female non‐smokers) from Stockholm and southern Sweden. Questionnaire data were collected for each participant, including work tasks for the hairdressers. We measured telomere length in peripheral blood leucocytes using quantitative PCR and DNA methylation status of genes relevant for bladder cancer using methylation sensitive high resolution melting analysis. The hairdressers had shorter telomeres ( β = −0.069, P = 0.019) compared with non‐hairdressers. Shorter telomeres were found in hairdressers up to 32 years old performing hair waving more than once per week as compared with hairdressers in the same age group performing hair waving less often ( β = −0.12, P = 0.037). Hair waving was associated with less frequent CDKN2A methylation (odds ratio, OR = 0.19, P = 0.033). Shorter telomeres in hairdressers may indicate a genotoxic effect. Performing hair waving was associated with short telomere length, although the effect was only observed in young hairdressers. No clear patterns were discerned with regard to DNA methylation of bladder cancer‐related genes. The observed changes of methylation were not all in the expected direction and warrant further investigation. Environ. Mol. Mutagen. 57:159–167, 2016. © 2015 Wiley Periodicals, Inc.